Mecanismos de exclusión de los pueblos originarios en los discursos y representaciones del Buen Vivir ecuatoriano y el Vivir Bien boliviano: el tutelaje y la desapropiación simbólica - Pérez-Gañán, R. (Revista Iberoamericana de Estudios de Desarrollo)
This article have tried to take a close look at the (re)construction of identity among the indigenous populations with regards to State discourses and practices in the Ecuadorian Buen Vivir and the Bolivian Vivir Bien. By way of methodology of discourse analysis, I attempt to shed light on the progressive homogenization of indigenous diversity within a model of the «ideal indigenous person», which serves economic development policies that, far from reaching true plurinationality, seem to continue with patterns of the tutelage and displacement that started with the era of colonization.